Non-contact lensless holographic reconstruction of diffractive intraocular lenses profiles - Vila-Andrés, Rosa; Martínez-Espert, Anabel; Furlan, Walter D.; Esteve-Taboada, José J.; Micó, Vicente (Scientific reports, 2025)
A lensless compact arrangement based on digital in-line holography under Gabor’s regime is proposed as a novel contactless method to assess the profile of multifocal intraocular lenses (MIOLs) which are conformed by several diffractive rings. Diffractive MIOLs are a widely adopted ophthalmologic option for the correction of presbyopia in patients undergoing cataract surgery. The MIOL optical design might introduce non-negligible optical performance differences between lenses as well as the introduction of undesirable photic phenomena (such as halos and glare) affecting the vision of users. Therefore, the customized topographic control of each manufactured MIOL model, along with the advancement of optical simulation routines, is increasingly necessary to provide users with optimized performance of these implanted optics, as well as predictable and realistic expectations of their future vision with these solutions. In this manuscript, experimental results of the reconstruction of different smooth and highly edged diffractive profiles from a pair of commercially available MIOLs are presented. Besides, a study evaluating the convergence and robustness of the proposed iterative phase-retrieval routine based on a modified classical Gerchberg-Saxton algorithm is performed. These results provide experimental validation of the proposed technique for accurately measuring the optical profiles of MIOLs.